Climate Data Tools (CDT) Training for the Ghana Meteorological Agency (GMet) - Faniriantsoa, Rija; Grossi, Amanda (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The CDT has so far been installed in 24 countries and two Regional Climate Centers (RCCs), including the IGAD Climate Prediction and Applications Centre (ICPAC) in East Africa which partook in the regional training. The intention of this workshop was to train the Ghana Meteorological Agency (GMet) in use of CDT. Training took place from March 30-April 9, 2022.